2019
DOI: 10.1007/s11012-019-00983-8
|View full text |Cite
|
Sign up to set email alerts
|

Random vibration mitigation of beams via tuned mass dampers with spring inertia effects

Abstract: The dynamics of beams equipped with tuned mass dampers is of considerable interest in engineering applications. Here, the purpose is to introduce a comprehensive framework to address the stochastic response of the system under stationary and nonstationary loads, considering inertia effects along the spring of every tuned mass damper applied to the beam. For this, the key step is to show that a tuned mass damper with spring inertia effects can be reverted to an equivalent external support, whose reaction force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This allowed the accuracy of the numerical method proposed in this paper to be discussed without presenting an extensive new series of numerical analyses. Studies conducted by Failla et al [33,36,37,44], Di Lorenzo et al [34,35], and Adam et al [12] confirmed that the method proposed in this paper is valid by providing exact solutions. When compared to the classical mathematical method, it should be noted that as all mathematical methods are an approximation, so when "exact solutions" are discussed, this term is in reference to the classical solution.…”
Section: Validation Of the Proposed Methodssupporting
confidence: 70%
See 2 more Smart Citations
“…This allowed the accuracy of the numerical method proposed in this paper to be discussed without presenting an extensive new series of numerical analyses. Studies conducted by Failla et al [33,36,37,44], Di Lorenzo et al [34,35], and Adam et al [12] confirmed that the method proposed in this paper is valid by providing exact solutions. When compared to the classical mathematical method, it should be noted that as all mathematical methods are an approximation, so when "exact solutions" are discussed, this term is in reference to the classical solution.…”
Section: Validation Of the Proposed Methodssupporting
confidence: 70%
“…To further attest to the validity of the proposed method, a number of other studies have applied the proposed method, namely [12,33,36,37,39,44,46]; these papers have shown the proposed method's formulation along with results of the dynamic response under various types of forcing actions.…”
Section: Validation Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the system excitation deviates significantly from the Gaussian distribution, the non-Gaussian characteristics of vibration must be accurately simulated [12]. Because of the extreme response of the system, especially sensitive to the high peak excitation of the load and the degree to which the response deviates from the Gaussian distribution, it will seriously affect the accumulation speed of system vibration fatigue damage [13]. The ARMA method is based on linear difference equations and simple calculation, but it cannot be displayed on irregular intervals; it has the characteristics of extremely large-amplitude pulse signals; therefore, it is not completely suitable for simulating non-Gaussian random time series [14].…”
Section: Introductionmentioning
confidence: 99%
“…The GFA has been extensively studied. Most recently on beams with various in-span supports and masses [17], on discontinuous layered elastically bonded beams [18], on plane structures with mass-spring subsystems and rotational joints [19] and on beams including tuned mass dampers with spring inertia effects [20].…”
Section: Introductionmentioning
confidence: 99%